A comparative and modeled approach for three biochar materials in simultaneously preventing the migration and reducing the bioaccessibility of heavy metals in soil: Revealing immobilization mechanisms. (15th September 2022) - Wang, Gehui; Tariq, Muhammad; Liang, Weiyu; Wan, Jiang; Peng, Cheng; Zhang, Wei; Cao, Xinde; Lou, Ziyang
Abstract: The effectiveness and feasibility of the three biochar materials for remediation of arsenic (As) and lead (Pb) contaminated soil were explored in this study. Significant reduction of bioaccessibility and migration risks of both heavy metals have been explained mechanistically by incubation, column experiments and numerical simulation. Langmuir equation fitted As and Pb sorption isotherms better in the control and biochar (BC) amended soils, while Freundlich model was more suitable for iron modified biochar (Fe-BC) and sulfur/iron modified biochar (S/Fe-BC) amended soils, indicating that modified biochar promoted chemical adsorption process for As and Pb. For the three biochar materials, S/Fe-BC showed the best effects on reducing the bioavailability of As and Pb, with a decrease of 40.42%–64.21%. The reduction in bioaccessibility by metal portioning into available and non-available fractions was better for illustrating the mechanisms including adsorption, precipitation/coprecipitation and As(III) oxidation behind S/Fe-BC efficacy. Moreover, S/Fe-BC can effectively inhibit the leaching behavior of As and Pb under acid rain, which increased by 99.89% and 90.18%, respectively, compared with the control. The HYDRUS-1D modeling indicated that S/Fe-BC could continuously treat As (100 mg/L) and Pb (1000 mg/L) contaminated water for 16.22 years and 40.86 years, respectively, and ensure the groundwater quality criteria being met. Based on these insights, we believe that our study will provide meaningful information about the potentials of biochar derived materials for soil heavy metals' remediation. Graphical abstract: Image 1 Highlights: Adsorption pattern of As and Pb changed in modified biochar amended soil. Effects on reducing As and Pb bioaccessibility were S/Fe-BC > Fe-BC > BC. S/Fe-BC effectively restrained As and Pb leaching in simulated acid rain. Site scale migration of immobilized As and Pb was simulated via HYDRUS-1D. Reduction of bioavailability and migration was attributed to morphological change.